Etiology, clinical profile in cortical venous thrombosis - Pazare, Amar R.; Karkera, Karan B (International Journal of Advances in Medicine, 2018)
Background: Cerebral venous sinus thrombosis (CVST) is increasingly recognized entity in young patients due to the widespread availability of MRI and rising clinical awareness. CVST is a multifactorial condition with a wide clinical presentation, variable etiologies and prognosis and it requires high index of suspicion for diagnosis. Methods: It is an observational prospective study conducted in 57 patients. Patients above 12 years of age with a diagnosis of cerebral venous sinus thrombosis were included in the study to know aetiology, risk factors, clinical presentation and prognosis. Results: Mean age for males was 40 years and for females it was 36.5 and male to female ratio was 3:2. Headache was the most common symptom (89.47%) followed by convulsions, vomiting, focal neurological deficit, altered sensorium, fever and papilloedema. Superior Sagittal Sinus was the most common sinus involved followed by transverse sinus. Common risk factors were Hyperhomocysteinemia, alcohol, tobacco, APLA syndrome. 52.63% of patients had complete neurological recovery. Conclusions: CVST is uncommon condition and it is more common in neonates, children and females. The major risk factors for CVT in adults are prothrombotic (hypercoagulable) conditions, oral contraceptives, pregnancy and the puerperium, malignancy, infection, head injury. Headache is the most common symptom may be accompanied by focal neurologic deficits, seizures, and encephalopathy. It carries 5% mortality in the acute phase and 10% over a long-term follow up.